Aplikasi Perhitungan Harga Pokok Produksi Dengan Metode Harga Pokok Proses Pada âUd. Barito Bakeryâ - Yoewono, Ivan Kurniawan; -, Yulia; Setiawan, Alexander (Jurnal Infra, 2015)
UD. Barito Bakery is an operated bread baking company. Currently, the company is using manual data recording system, which will cause several problems to occur. The calculation of the cost of production is also done manually by taking into account the raw materials used in production, without considering the factory overhead costs and labor costs. The manual calculation of the cost of production will also cause several problems and will affect the profit obtained by the company.Based on the background of these problems, the system for calculating the cost of production is designed. The system design of the application is going through several stages; begin by conducting survey of bread production systems, analyzing data, and designing the Data Flow Diagram and Entity Relationship Diagram. The application process is completed by using Microsoft Visual Studio .Net 2012Â as programming languages and PostgreSQL as database. The calculation of the cost of production is done by using Process Costing method.The results obtained from this application is that it can store all data related to the production process, purchasing, sales, automatic calculation of the cost of production, as well as card stock that can be updated automatically.